Cryptographic models of nanocommunicaton network using quantum dot cellular automata: A survey - Bikash Debnath; Jadav Chandra Das; Debashis De (IET Quantum Communication, 2021)
Abstract Security of information is an important issue during the transmission of information. The device that performs the encoding and decoding process is called the encoder and decoder, respectively. The major issues to develop such devices are circuit complexity and power dissipation at the nanoscale level. This can be fixed by utilising the features of reversible logic with Quantum dot cellular automata (QCA) device as a promising archetype for an alternative to the traditional transistor‐based device. QCA has high protection against side‐channel attacks, especially from power analysis attacks. All those features of QCA influence the researchers to explore several QCA‐based cryptographic models of nanocommunication for secure data transmission. Here, the existing QCA‐based circuits for cryptographic architecture are explored and compared concerning their circuit complexity, device area, and operating speeds. The working principles of each of those existing architectures have been demonstrated in detail. Besides, the embedding of reversible logic in QCA cryptographic architecture is also explored. The architectures are compared in terms of the logic used in the design. Finally, the major key issues are identified and addressed in the context of cryptographic models for future secure data transmission processes.